Upaya Guru Dalam Meningkatkan Hasil Belajar Bahasa Arab Peserta Didik Melalui Metode Pemberian Tugas Selama Pandemi Covid-19 Di MA Al-Ikhwan Topoyo - Muhammad Nur Asmawi; Nur Azisah (Albariq: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to determine the teacher's efforts in applying the assignment method in learning Arabic and whether there is an increase in student learning outcomes through the assignment method and how learning is implemented during the co-19 pandemic. The method used in this study is a qualitative descriptive method that describes the teacher's efforts to improve students' Arabic learning outcomes through the assignment method during the co-19 pandemic at MA Al-Ikhwan Topoyo. The results showed that the teacher's efforts in implementing learning through the method of giving assignments during the Covid-19 pandemic went through three stages, namely the preparation stage, the implementation stage, and the completion stage (assessment and evaluation). The implication of this research is that in preparing for giving assignments in learning, it is necessary to prepare teachers with appropriate plans and tools and learning media so that there are no obstacles in carrying out learning and producing maximum results and students are expected to be more active and enthusiastic in the learning process.